Gallery RJ’s Promotion Strategy Through Instagram Social Media in Building Brand Awareness in Bengkulu City - Iftahul Jannah; Djoesept Harmat Tarigan (Asosiasi Dosen Muda Indonesia, 2026)
The rapid development of digital technology has transformed business promotion practices, particularly through social media platforms. Instagram has become an effective promotional medium for businesses to introduce products, communicate with consumers, and strengthen brand awareness. This study aims to analyze the promotional strategy implemented by Gallery RJ through Instagram in building brand awareness in Bengkulu City. This research used a descriptive qualitative approach with a case study design. Data were collected through interviews with Gallery RJ customers, observation of the Instagram account @galleryrjbengkulu, content analysis, documentation, and literature review. The data were analyzed using the AISAS model, consisting of Attention, Interest, Search, Action, and Share. The findings show that Gallery RJ utilizes Instagram features such as feeds, stories, reels, highlights, captions, hashtags, product demonstrations, and discount information to attract consumer attention and encourage interaction. Consistent product uploads, affordable prices, attractive visual content, and customer testimonials contribute to consumer interest and brand recognition. The study also found that customers tend to search for product information through Instagram, direct messages, WhatsApp, and recommendations from friends or family before making purchase decisions. Furthermore, customers often share promotional information and shopping experiences, which supports word-of-mouth promotion. These findings indicate that Gallery RJ’s Instagram promotional strategy has contributed positively to building brand awareness among consumers in Bengkulu City, although further development is needed in terms of customer interaction, influencer collaboration, and Instagram analytics optimization.